Model Pembelajaran Berbasis Masalah Sebagai Upaya Meningkatkan Kemampuan Berpikir Kritis Siswa - Siren Nugroho; Prisna Pritalora; Martha Tesalonika (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to investigate the implementation of Problem Based Learning (PBL) and its effect on enhancing students’ critical thinking skills. The research employs a qualitative descriptive method with data collection from classroom observations and student assessments. PBL is characterized by engaging students actively in solving real-life problems, promoting analytical and independent thinking. The findings reveal that PBL significantly improves students’ critical thinking abilities by stimulating adaptive and analytical thinking processes, encouraging collaboration, and fostering metacognitive skills. Despite requiring more time and student readiness for independent learning, PBL proves to be an effective model for creating meaningful and contextual learning experiences. The role of teachers as facilitators is crucial to support and guide students throughout the problem-solving stages. This study supports the use of PBL as a strategic approach in education to develop higher-order thinking skills applicable to real-world challenges.